2014
DOI: 10.1039/c4ra00526k
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the efficiency of diastereoisomer separation on the basis of the behaviour of enantiomeric mixtures

Abstract: The driving force of homo-and heterochiral complex formation in mixtures of chiral compounds is, probably, the effort of the system to separate the most symmetric associates from the less symmetric ones. A possible way to achieve separation of these associates is distribution between two phases. Therefore, during the separation of (a certain part) diastereoisomers similar trends can be observed as in the course of the distribution of enantiomeric mixtures between two phases, although in the first case a third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
(22 reference statements)
0
18
0
Order By: Relevance
“…[10,11] It was discovered that the maximum optical purity that can be reached in a single resolution step correlates to the melting point eutectic composition of the racemate or the resolving agent, depending on which one is higher. [12] A limit corresponding to the melting point eutectic composition was also found in the recrystallization-based further purification of enantiomeric mixtures under atmospheric conditions. [11] Certain types of supercritical carbon dioxide-involving processes for optical resolution have already been published.…”
Section: Introductionmentioning
confidence: 84%
“…[10,11] It was discovered that the maximum optical purity that can be reached in a single resolution step correlates to the melting point eutectic composition of the racemate or the resolving agent, depending on which one is higher. [12] A limit corresponding to the melting point eutectic composition was also found in the recrystallization-based further purification of enantiomeric mixtures under atmospheric conditions. [11] Certain types of supercritical carbon dioxide-involving processes for optical resolution have already been published.…”
Section: Introductionmentioning
confidence: 84%
“…The behaviour of enantiomeric mixtures can be described as racemic-like, (about 80%), and conglomerate-like behaviour (about 20%) [3,4] A non-linear correlation can be seen between the purity of the crystallized mixture and the initial composition, both the melting point diagrams and purity-purity diagrams are specific for a given behaviour [5,6].…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] Fogassy and colleagues found that the optical purity of the enantiomers obtained in several diastereomeric resolutions via slow atmospheric crystallization shows good correlation with the melting eutectic composition (ee) of the resolving agent or the racemic compound, depending on which one is higher. 16 It is also known that the recrystallization-based purification of nonracemic enantiomeric mixtures is often limited at the same composition as the melting point eutectic of the compound. 17 Besides presenting gas antisolvent fractionation as a novel diastereomeric enrichment technique, we aim to investigate whether the atmospheric melting point phase diagram and the high-pressure purification results might be correlated.…”
Section: Introductionmentioning
confidence: 99%